Mystery Of The Tolling Bell - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1946)
Nancy, along with Bess and George, investigates spooky, phantom bell tolls and a "ghost" haunting a seaside cave in Candleton.
Keywords: Nancy Drew$1 (Bis defined by self-sufficiency, level-headedness, and a balance between action and intellect. s; primarily a juvenile mystery, the novel delves into themes of greed, justice, and community moral responsibility through a plot centered on fraud and hidden secrets